Hadih Maja Aceh from the perspective of Cheryll Glotfelty’s ecocriticism and its utilization in the development of Acehnese language and literature teaching materials in higher education - Saputra, Nanda; Suwandi, Sarwiji; Setiawan, Budhi (Research Journal in Advanced Humanities, 2025)
The objective of this study was to reintroduce the Acehnese oral poetry Hadih Maja to the younger generation, particularly university students, in a different format and as a subject in higher education. A descriptive qualitative approach was implemented in this study. The data sources for this research were informants and documents. The informants are the research data sources with the following criteria: (1) comprehensive mastery of Hadih Maja; (2) male and female; (3) mastery of the Acehnese language; (4) over 40 years of age, physically and mentally healthy; and (5) the community members requested for Hadih Maja data reside in Pidie Regency. After analyzing the data, the researchers found 34 Hadih Maja data containing the existence of literary ecology and values. The data were grouped based on their respective types consisting of (1) 25 natural ecology data (EA); including 17 data containing the relationship between literature and nature (SA) and 8 data containing the relationship between literature and humans (SM), (2) 7 cultural ecology data (EB); including 6 data containing the relationship between literature and customs (SAI) and 1 data containing the relationship between literature and beliefs/myths (SK) as well as 4 data containing moral, cultural, religious and social values.